2012
DOI: 10.1017/s0305741012000379
|View full text |Cite
|
Sign up to set email alerts
|

Death versus GDP! Decoding the Fatality Indicators on Work Safety Regulation in Post-Deng China

Abstract: This article examines how Chinese reformers have used a set of "fatality indicators" to deal with the serious work safety situation in the past two decades. It argues that the system of fataUty indicators is a prudent strategy to tackle the responsibility deficiencies in the previous work safety regulatory system and strengthen the central government's supervision over local safety management. The primary purpose of implementing the fatality indicators is to shift local officials' focus from a GDP-centred grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…While local officials of good performance had a higher chance of promotion (Gao 2009), low performance may lead to despise and punishment. A result-oriented and pressure-driven system was created along the hierarchy (Chan and Gao 2012). Such pressure was also strengthened by competition among peers.…”
Section: Performance Measurementmentioning
confidence: 99%
“…While local officials of good performance had a higher chance of promotion (Gao 2009), low performance may lead to despise and punishment. A result-oriented and pressure-driven system was created along the hierarchy (Chan and Gao 2012). Such pressure was also strengthened by competition among peers.…”
Section: Performance Measurementmentioning
confidence: 99%
“…High-performing local elites are selected to move upward (Gao, 2009;Guo, 2007). From central to township governments, 6 a result-oriented PM system continuously disaggregates and assigns PM targets (Chan & Gao, 2012), replacing the old planning system that directly controlled local resources and activities. Consistent downward PM pressures are imposed from above.…”
Section: Decentralization and Intergovernmental Gamingmentioning
confidence: 99%
“…These targets first appeared in local governments' performance assessments in 2004, following the central leaders' establishment of the Work Safety Commission of the State Council in 2003 to deal with the serious work safety situation in local China. Since then, the Work Safety Commission has developed a group of fatality indicators (work safety control evaluation indicators) on an annual basis and assigned these targets to local governments at all levels (Chan & Gao, 2012). Table 1 Targets for social stability assigned to Zhouzhi County in 2010.…”
Section: Top-down Target Allocationmentioning
confidence: 99%
“…As some studies have shown, Chinese leaders in the reform era have relied heavily on this system as a political instrument to enhance the party-state's capacity to ensure policy compliance across the vast local bureaucracy (Burns & Zhou, 2010;Edin, 2003;Gao, 2009). The result has been both impressive progress and serious problems in local governance (Chan & Gao, 2012;O'Brien & Li, 1999). Despite the valuable contributions of these studies, they provide inadequate discussion of how the TRS's political function affects its technical power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation